Cerebrospinal fluid inflammatory profile of cognitive impairment in newly diagnosed multiple sclerosis patients. (April 2022) - Pitteri, Marco; Magliozzi, Roberta; Nicholas, Richard; Ziccardi, Stefano; Pisani, Anna Isabella; Pezzini, Francesco; Marastoni, Damiano; Calabrese, Massimiliano
Background: The cerebrospinal fluid (CSF) molecular milieu is a marker of diffuse intrathecal inflammation in the meninges that, in turn, targets the grey matter (GM) in multiple sclerosis (MS). Cognitive impairment (CI) is associated with brain damage in MS and is often present early in people with MS (pwMS). Objective: To investigate whether a specific CSF inflammatory profile is associated with different degrees of CI in newly diagnosed pwMS. Methods: Sixty-nine pwMS and 43 healthy controls (HCs) underwent neuropsychological testing. The presence and levels of 57 inflammatory mediators in the CSF were assessed. Results: Apparently cognitively normal (ACN) pwMS had impaired executive functioning compared to HCs but performed better than pwMS with mild and severe CI (mCI and sCI) in all tests. CSF mediators involving innate immunity and immune activation and recruitment, differentiate ACN from pwMS with mCI, while CSF mediators related to B- and T-cell immunity and chemotaxis differentiate both ACN and mCI from those with sCI. CXCL13 was the only molecule that differentiated sCI from mCI pwMS. Conclusion: Specific CSF molecular patterns, reflecting the involvement of both innate and adaptive immune responses, are associated with the severity of CI in newly diagnosed pwMS.